Review of Testudobracon Quicke (Hymenoptera: Braconidae) with descriptions of four new species from south India - Sheeba, M.; Ranjith, A.p.; Narendran, T.c. (Zootaxa, 2017)
The Braconinae is a generically diverse subfamily of Braconidae. The Old World genus Testudobracon Quicke is reviewed and four new species viz., T. athashi Ranjith sp. nov., T. malabaricus Sheeba sp. nov., T. shameeri Ranjith sp. nov. and T. travencorensis Sheeba sp. nov., are described from south India. A check list and key to the world species are provided.